Motor Pompa DC Sebagai Mesin Alat Pengaduk Pada Proses Koagulasi - Lelboi, Jefrianus; Kadaria, Ulli; Pramadita, Suci (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Jalan Purnama II in South Pontianak District to meet the needs of MCK, peat groundwater is used as the source of water. The study area's peat water quality measures pH 6.04, turbidity 10.54 NTU, colour 500 TCU, and organic matter 322 mg/L. Water quality does not meet Permenkes No.32 Tahun 2017 and Permenkes No.2 Tahun 2023 quality standards. The study's goal is to determine the quality of raw water before and after processing, as well as the effect of time on coagulant mixing results. A mechanical stirring machine with a 12-volt DC pump motor spinning at 3000 rpm and a rod length of 60 cm speeds up the process of mixing raw water with 72 grams of alum coagulant and 216 grams of quicklime. The sedimentation process lasts one hour, followed by filtration with 40 cm of shell sand as media and a contact time of one minute.The jar test was used to determine the alum and quicklime doses. The stirring time was varied from T1 to T5 to T10. The test parameters are pH,turbidity,colour,and organic matter. The best pH,turbidity,and colour values were found at T1, with pH 10.78,turbidity 1.92 NTU and colour 230 TCU, and the best organic substance parameters at T5 298 mg/L. The turbidity parameter meets the Permenkes No.2 Tahun 2023 quality standard,meanwhile organic substances do not yet meet Permenkes No.32 Tahun 2017 quality standards,and pH and colour parameters do not meet Permenkes No.2 Tahun 2023 standards. Beside on the result,T1 has the best time variation.